Giving Boiled Celery Leaves to Reduce Blood Pressure in Elderly People with Hypertension - M Syikir; Tri Wulansari Dewi; Adiatman Adiatman; Irfan Irfan (Jurnal Vocational Nursing Sciences (VNUS), 2021)
The high incidence of hypertension in the elderly and uncontrolled triggers degenerative diseases such as congestive heart failure, kidney failure, and vascular disease such as stroke and peripheral arterial disease. The high incidence of hypertension is directly proportional to the high complications that occur, so adequate nonpharmacologic treatment is needed. Celery (Apium graveolens L.) is one of the types of herbal therapy used to treat hypertension. Traditional Chinese society has long used celery to lower blood pressure. The purpose of this study was to determine the effect of celery leaf decoction on elderly blood pressure in patients with hypertension in the Mambi Health Center, Mamasa District. His research method is a quasi-experimental method, using a time-series research design. This study took a sample of 20 people. The sampling techniques were consecutive sampling, and the measuring instruments used were observation sheets and spigmanometers. Analyzed by the Friedman test with a significance level of alpha = 0.05. The results of the study obtained statistical tests showing that there were significant differences by comparing systolic blood pressure before, 3 days of administration and 7 days of administration of celery leaves, obtaining a mean value which decreased from the first day, the third day and the days of 2.75, 2.23 and 1.03 with a value of 0.000 <0.05, as well as Diastolic blood pressure, respectively, 2.75, 1.98 and 1.30 with p value of 0.000 <0.05, which means there is an effect of giving celery leaf decoction to reduce systolic and diastolic blood pressure